2021
DOI: 10.1002/adfm.202009848
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Calcium Phosphate Nanotheranostics with Tumor‐Specific Activatable Cascade Catalytic Reactions‐Augmented Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is exploited as a promising strategy for cancer treatment. However, the hypoxic solid tumor and the lack of tumor-specific photosensitizer administration hinder the further application of oxygen (O 2)-dependent PDT. In this study, a biodegradable and O 2 self-supplying nanoplatform for tumor microenvironment (TME)-specific activatable cascade catalytic reactions-augmented PDT is reported. The nanoplatform (named GMCD) is constructed by coloading catalase (CAT) and sinoporphyrin sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 35 publications
0
80
0
Order By: Relevance
“…Furthermore, O 2 generation overcomes tumor hypoxia and improves PDT induced generation of 1 O 2 . These NPs showed selective accumulation at tumor sites monitored by FLI as well as Mn +2 mediated MRI 65 . In another study, Jiang et al, reported biocompatible polymeric NPs, pluronic F127 encapsulated hexyloxyethyl-devinyl pyropheophorbide-a (HPPH) and camptothecin (chemotherapeutic drug), whereby the NPs are selectively activated by ROS at the tumor site.…”
Section: Theranostics: ''Multifunctional Agents'' For Image-guided Photodynamic Therapymentioning
confidence: 99%
“…Furthermore, O 2 generation overcomes tumor hypoxia and improves PDT induced generation of 1 O 2 . These NPs showed selective accumulation at tumor sites monitored by FLI as well as Mn +2 mediated MRI 65 . In another study, Jiang et al, reported biocompatible polymeric NPs, pluronic F127 encapsulated hexyloxyethyl-devinyl pyropheophorbide-a (HPPH) and camptothecin (chemotherapeutic drug), whereby the NPs are selectively activated by ROS at the tumor site.…”
Section: Theranostics: ''Multifunctional Agents'' For Image-guided Photodynamic Therapymentioning
confidence: 99%
“…[ 3 ] Therefore, many efforts have been made to improve the efficacy of GOx‐mediated starvation efficacy. For example, catalysts such as MnO 2 [ 4 ] and catalase [ 5 ] were used to convert H 2 O 2 to H 2 O and O 2 to improve the local oxygen pressure, which could subsequently promote the catalytic activity of GOx. Unfortunately, for this strategy, the improved oxygen pressure was at the price of sacrificing the toxic H 2 O 2 , which will make the treatment less effective.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, ultrasound (US) exposure is devoted to clinical diagnostic imaging; on the other hand, acoustic luminescence from the US-mediated cavitation effect activates sonosensitizers to generate ROS, thus inducing cell apoptosis/necrosis caused by DNA fragmentation, cytoskeletal shrinkage and chromatin condensation 27 , 28 . In addition, a high level of ROS depletes the antioxidant GSH, causing lipid peroxidation and leading to the initiation of ferroptosis 29 , 30 . Among various types of organic and inorganic sonosensitizers, IR780, a lipophilic heptamethine dye with a peak optical absorption at 780 nm, is considerably appealing for clinical practice owing to its high fluorescence quantum yield, elevated US-triggered ROS generation efficiency, excellent aqueous stability and preferential accumulation in tumors 31 - 33 .…”
Section: Introductionmentioning
confidence: 99%